2016
DOI: 10.1038/srep19556
|View full text |Cite
|
Sign up to set email alerts
|

Association between Carotid Intima-Media Thickness and Cognitive Impairment in a Chinese Stroke Population: A Cross-sectional Study

Abstract: This study aimed to investigate the potential associations between carotid intima-media thickness and cognitive impairment among patients with acute ischemic stroke and to identify the clinical implications. We measured carotid intima-media thickness (IMT) and performed the Mini-Mental State Examination (MMSE) upon the admission of 1,826 acute ischemic stroke patients. The association between IMT and cognitive impairment evaluated by the MMSE was assessed with a multivariate regression analysis. Other clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…As described above, functional MRI [40] showed pathological cerebral alterations in RA. In non-RA, stroke patients, other investigators also found associations between cognitive decline and carotid atherosclerosis [41]. Cerebral blood flow in association with cognitive function has not yet been assessed in RA before.…”
Section: Discussionmentioning
confidence: 98%
“…As described above, functional MRI [40] showed pathological cerebral alterations in RA. In non-RA, stroke patients, other investigators also found associations between cognitive decline and carotid atherosclerosis [41]. Cerebral blood flow in association with cognitive function has not yet been assessed in RA before.…”
Section: Discussionmentioning
confidence: 98%
“…The design and main results of the Study of Oxidative Stress in Patients with Acute Ischemic Stroke (SOS‐Stroke) have been described in detail previously . In brief, SOS‐Stroke was a prospective, multicenter registry that consisted of consecutively selected patients ( n = 4164) with acute ischemic stroke.…”
Section: Methodsmentioning
confidence: 99%
“…Recent large-scale studies have shown that an increased cIMT value is generally associated with future cerebrovascular events, independent of age and sex [23, 45, 48]. However, a few reports have questioned the role of cIMT as a predictor of cardiovascular events [49]; the most recent meta-analysis of 14 population-based studies reported a hazard ratio of 1.09 for the first myocardial infarction/stroke per every 0.1 mm increase in the cIMT [48]. One plausible explanation for this controversy may lie in the location of the cIMT measurement [50], as carotid bulb cIMT values were positively associated with future cardiac events; however, cIMT values measured in the distal wall of the common carotid artery failed to predict coronary events [43].…”
Section: Discussionmentioning
confidence: 99%